Land litigations: The case of the Resguardo of Chivatá in the second half of the 18th century (2021)
In the Viceroyalty of New Granada, during the second half of the 18th century, the Resguardo of Chivatá was involved in a series of land litigations, related to confusion about the borders, leading to the invasion of communal lands by neighbours and the invasion of the indigenous people of lands bordering the resguardo. The objective of this article is to analyse, through the documentary interpretation of primary sources, the lawsuits around this resguardo, making special emphasis in that which the Augustine friars were implicated, given the singularity of the lawsuit with a religious congregation. Also, it is sought to establish how the conflict indirectly contributed to the continuity of the resguardo, at least until the beginning of the 18th century. Thus, the locals conserved the assigned territory and also managed to obtain an extension to its borders.